2006
DOI: 10.3732/ajb.93.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and size relations: an essay on the apple (Malus × domestica, Rosaceae) tree

Abstract: The influence of tree size independent of age on some architectural features (annual shoot length, lateral branching, flowering) was investigated on 4-yr-old apple (Malus × domestica) trees either own-rooted or grafted on the dwarfing rootstock M.9, giving rise to large and small trees, respectively. Tree size significantly affected the length of the first annual shoot of bottom branches with a lesser effect on the subsequent annual shoots of the same branches and on branches situated higher in the tree canopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 47 publications
3
17
0
2
Order By: Relevance
“…Tree height of 'Conference' was much higher than that reported by Kobelus (2002) for the same cultivar (Table 1). Vegetative growth is based on the genetic constitution of species and/or cultivars Lauri et al, 1995Lauri et al, , 2006, the fact testifying to significant differences in TH observed among the cultivars in both the seasons (Table 1), as previously observed by Jacyna (2004). Moreover, the differences in TH are also attributable to the effect of different levels and proportions of auxin and cytokinin in the apical meristem in different pear cultivars (Wang et al, 1994).…”
Section: Analysis Of Nursery Tree Height and Trunk Diametersupporting
confidence: 61%
See 1 more Smart Citation
“…Tree height of 'Conference' was much higher than that reported by Kobelus (2002) for the same cultivar (Table 1). Vegetative growth is based on the genetic constitution of species and/or cultivars Lauri et al, 1995Lauri et al, , 2006, the fact testifying to significant differences in TH observed among the cultivars in both the seasons (Table 1), as previously observed by Jacyna (2004). Moreover, the differences in TH are also attributable to the effect of different levels and proportions of auxin and cytokinin in the apical meristem in different pear cultivars (Wang et al, 1994).…”
Section: Analysis Of Nursery Tree Height and Trunk Diametersupporting
confidence: 61%
“…However, the apple rootstock/cultivar interactions suggested that overall growth was controlled by the rootstock (Ferree et al, 2001). The above results could be rationally attributed to the specific effect of the cultivar of a specific fruit species Lauri et al, 1995Lauri et al, , 2006. The TD is used to calculate the trunk cross-sectional area (TCSA), both values testifying to the strength of the tree growth.…”
Section: Analysis Of Nursery Tree Height and Trunk Diametermentioning
confidence: 99%
“…In general, dwarfing rootstocks can effectively control scion vigour and reduce plant height, thus resulting in smaller trees (Lauri et al 2006;Tworkoski and Miller 2007). It has also been reported that the growth rate of scion cultivar can be independent of rootstock (Bulley et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Rootstocks have a special value for fruit production as they can effectively control tree size, influence growth and development of cultivars grafted onto them and tolerate adverse soil conditions (Drake et al 1988;Fallahi et al 1985;Ferree et al 2001a, b;Ferree 1995, 1996;Lauri et al 2006;Tubbs 1974;Tworkoski and Miller 2007;Webster et al 1985). However, there are no ideal rootstocks available for commercial production and genetic improvement of existing rootstocks or breeding new rootstocks is thus a continuous goal for fruit tree breeding.…”
Section: Introductionmentioning
confidence: 97%
“…Regardless, spur-type apple cultivars undoubtedly moderately reduced tree size as compared to standard-type trees (Costes et al, 2010). Unlike dwarfing rootstocks that reduce the proportion of lateral buds that develop into long shoots during the early development of trees (Lauri and Trottier, 2006; Seleznyova et al, 2008), YF produces a dwarf tree architecture by reducing the duration of shoot vegetative growth and shortening internode length.…”
Section: Discussionmentioning
confidence: 99%